Do good, goes bad, gets ugly: Kony 2012. Issue 2 (3rd June 2013) - Bal, Anjali S.; Archer‐Brown, Chris; Robson, Karen; Hall, Daniel E.; Plangger, Kirk; Mills, Adam J.
<x xml:space="preserve">Abstract</x> With millions of videos with different messages uploaded per year, companies are increasingly looking for means of making their messages stand against competitors. A theory of viral marketing is used to analyze and understand the spread of—and reactions to—a controversial political mega‐viral video, Kony 2012. Through this analysis, policy makers and marketers could gain a better understanding of how they can use mediums such as YouTube to extend their messages. Kony 2012 concerns the highly publicized leader of a Ugandan guerrilla group, Joseph Kony. The video was a call to action and an attempt to educate the world about the atrocities committed in Sudan. The video was made by an organization called the Invisible Children and created by filmmaker Jason Russell. Following the extraordinary success of Kony 2012, Jason Russell was infamously arrested in San Diego for indecent exposure. The story and video of Russell's arrest and breakdown similarly went viral. The framework that follows analyzes the virality of a political video and the downfall of its creator. Copyright © 2013 John Wiley & Sons, Ltd.